An Investigation into Rigidity–Activity Relationships in BisQAC Amphiphilic Antiseptics. (18th December 2018) - Kontos, Renee C.; Schallenhammer, Stephanie A.; Bentley, Brian S.; Morrison, Kelly R.; Feliciano, Javier A.; Tasca, Julia A.; Kaplan, Anna R.; Bezpalko, Mark W.; Kassel, W. Scott; Wuest, William M.; Minbiole, Kevin P. C.
Abstract: Twenty‐one mono‐ and biscationic quaternary ammonium amphiphiles (monoQACs and bisQACs) were rapidly prepared in order to investigate the effects of rigidity of a diamine core structure on antiseptic activity. As anticipated, the bioactivity against a panel of six bacteria including methicillin‐resistant Staphylococcus aureus (MRSA) strains was strong for bisQAC structures, and is clearly correlated with the length of non‐polar side chains. Modest advantages were noted for amide‐containing side chains, as compared with straight‐chained alkyl substituents. Surprisingly, antiseptics with more rigidly disposed side chains, such as those in DABCO‐12, 12, showed the highest level of antimicrobial activity, with single‐digit MIC values or better against the entire bacterial panel, including sub‐micromolar activity against an MRSA strain. Abstract : Connecting the dots to increase rigidity and antiseptic activity: Twenty‐one biscationic quaternary ammonium compounds (bisQACs) were prepared to assess the correlation between core rigidity and antimicrobial activity. The relatively floppy TMEDA is "tethered" by connecting two methyl groups, leading to a piperazine group; repeating this transformation provides DABCO. To our surprise, increased rigidity in the QAC antiseptics built from the piperazine and DABCO cores led to improved activity against both Gram‐positive and Gram‐negative bacteria.